Changes in the medical treatment status of Japanese outpatients during the coronavirus disease 2019 pandemic. (16th March 2021) - Takakubo, Takeshi; Odagiri, Yuko; Machida, Masaki; Takamiya, Tomoko; Fukushima, Noritoshi; Kikuchi, Hiroyuki; Amagasa, Shiho; Nakamura, Itaru; Watanabe, Hidehiro; Inoue, Shigeru
Abstract: Background: The coronavirus disease 2019 (COVID‐19) has a tremendous influence in general public's behaviors; however, changes in the status of regularly scheduled outpatient visits in Japan during COVID‐19 pandemic are still unknown. Methods: This cross‐sectional study was conducted in May 2020. Participants were recruited by an Internet‐based survey company. A total of 659 patients (54% male, average age 60 ± 14 years) who had regularly scheduled outpatient visits prior to the onset of COVID‐19 were enrolled. Participants answered four questions ("decrease in medical visit frequency, " "inability to take regular medication, " "deterioration of a chronic disease, " and "utilization of telephone/online medical care") and stated whether they had a fear of acquiring infection at a medical facility. The associations between answers, fear of infection, and socio‐demographic factors were examined. Results: Among the participants, 37.8% had decreased their medical visits, 6.8% were unable to take regular medications, 5.6% experienced a deterioration of chronic disease, and 9.1% utilized telephone/online medical care. Fear of being infected by COVID‐19 at medical facilities was strongly associated with a reduced frequency of medical visits and lack of regular medications even after adjusting for socio‐demographic factors and current medical histories. Conclusions: During the first wave of COVID‐19, approximately 40% of participants reduced their frequency of medical visits. It is important to continue implementing thorough infection control measures at facilities and educating the public the importance of keeping chronic diseases in good condition, as well as promoting telephone/online medical care. Abstract : We conducted an Internet survey of 2, 400 Japanese men and women in May 2020 and analyzed changes in the medical visit behavior/status of 659 people who had regularly visited to medical institutions before the coronavirus disease 2019 pandemic. Among the participants, 37.8% had decreased their medical visits, 6.8% were unable to take regular medications, 5.6% experienced a deterioration of chronic disease, and 9.1% utilized telephone/online medical care.